2015
DOI: 10.1007/s00586-015-4182-9
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality intraoperative neuromonitoring in extreme lateral interbody fusion. Transcranial electrical stimulation as indispensable rearview

Abstract: Monitoring the complete nervous system during an XLIF procedure is found to be helpful since nerve roots, lumbar plexus as well as the intradural neural structures may be at risk. TESMEP has additional value to sEMG and tEMG during XLIF procedure: (1) it informed about otherwise unnoticed events, and (2) it confirmed and added information to events measured using sEMG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…21 Additionally, a multimodal IONM strategy utilizing MEPs or saphenous SSEPs to monitor the lumbar plexus may be promising strategies based on results from a limited number of studies. 30,33,34,37 However, the additive benefit of multimodal IONM during LLIF remains without consensus and whether the increased cost of multimodal IONM justifies the unknown clinical benefit is without consensus. Ultimately, prospective studies, with clear definitions of postoperative neurologic injury, that evaluate different unimodal or multimodal IONM strategies are needed to accurately assess the efficacy of IONM during LLIF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Additionally, a multimodal IONM strategy utilizing MEPs or saphenous SSEPs to monitor the lumbar plexus may be promising strategies based on results from a limited number of studies. 30,33,34,37 However, the additive benefit of multimodal IONM during LLIF remains without consensus and whether the increased cost of multimodal IONM justifies the unknown clinical benefit is without consensus. Ultimately, prospective studies, with clear definitions of postoperative neurologic injury, that evaluate different unimodal or multimodal IONM strategies are needed to accurately assess the efficacy of IONM during LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…33 Further analysis revealed that MEP monitoring decreased both sensory and motor deficits and the authors suggested that MEPs can provide an indirect assessment of sensory nerve fiber integrity by monitoring mixed sensory-motor nerves that originate off the lumbar plexus. 33 In a smaller study, without a control group, Berends et al 34 reviewed 23 patients undergoing LLIF who were monitored with EMG and MEPs, and found that in 9% of patients MEP amplitude decreased due to psoas retractor deployment, without a corresponding change in EMG signals. However, whether additive MEP changed postoperative neurologic outcomes was unclear.…”
Section: Motor-evoked Potentialsmentioning
confidence: 99%
“…Transcranial electrical motor evoked potentials (tceMEPs) have played a role in the operating room since it was first demonstrated that the pulse-train stimulation technique could successfully evoke MEPs in the anesthetized patient [ 31 , 55 ]. While routine use of tceMEP monitoring began in spinal surgery in the 1980s, it is now also commonly used in many supratentorial [ 56 61 ] and infratentorial [ 62 66 ] procedures, as well as procedures in which peripheral nerves or spinal nerve roots are at risk [ 67 69 ]. Given the limitations of EEG and SSEPs mentioned above, the addition of tceMEPs to the multimodality IONM plan can paint a more comprehensive picture of nervous system function when monitoring cases using the EEA.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13] Therefore studies have been designed to investigate the utility of multimodal intraoperative neuromonitoring (IONM) techniques to decrease the incidence of postoperative neurologic complications and some of these studies have demonstrated additive benefit of utilizing somatosensory evoked potentials (SSEP) or motor evoked potentials (MEP) during LLIF surgery. [14][15][16][17] However, other studies question the utility of IONM during LLIF approaches, and have demonstrated comparable complication rates without utilizing any form of IONM. 18 The purpose of this study was to review neuromonitoring alerts in a large series of patients undergoing LLIF and determine whether alerts occurred more frequently when more lumbar levels were accessed and if alerts occurred more frequently at particular lumbar levels.…”
Section: Introductionmentioning
confidence: 99%